ANGPTL3 as a target for treating lipid disorders in type 2 diabetes patients - Jingfei Chen; Qin Luo; Yanfeng Yi; Jiangang Wang; Pengfei Chen; Fei Luo; Zhenfei Fang (Lipids in Health and Disease)
Abstract Type 2 diabetes mellitus (T2DM) is a globally prevalent metabolic disorder, and cardiovascular disease (CVD) is a significant cause of mortality and morbidity in diabetic individuals. In addition to hyperglycemia, lipid abnormalities associated with T2DM play a crucial role in the development of CVD complications. Diabetic dyslipidemia is characterized by elevated levels of triglyceride (TG)-rich lipoproteins and small dense low-density lipoprotein (LDL) particles, reduced high-density lipoprotein (HDL) cholesterol, and impaired HDL function. Angiopoietin protein-like 3 (ANGPTL3) is a liver-derived protein that plays a crucial role in regulating plasma lipoprotein metabolism by inhibiting lipoprotein lipase and influencing lipid levels. Inhibiting ANGPTL3 has shown promising effects in promoting HDL-mediated cholesterol reverse transport and reducing the levels of TG-rich lipoproteins and LDL cholesterol. Here, we explore the potential of ANGPTL3 as a therapeutic target for lipid management in T2DM patients.